The effect of job search requirements on welfare receipt - Nicolas Hérault; Ha Vu; Roger Wilkins (Global Labor Organization (GLO), 2020)
Many countries impose job search requirements as a condition of unemployment benefit receipt, but there is relatively little evidence on the efficacy of these requirements. Australian reforms in 1995 and 2003 saw groups of welfare recipients newly subjected to job search requirements, providing an opportunity to identify their effects on welfare receipt. Using this quasi-experimental design and administrative data, we find negative effects on welfare receipt for the mature-age partnered women targeted by the reforms. We also find large negative effects on welfare receipt of their partners, suggesting family labour supply decisions were considerably affected.
Keywords: H31; D10; J65; 330; welfare receipt; unemployment benefit; job search requirements